Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Sikap Tentang Senam Nifas Pada Ibu Hamil Trimester Iii Di Puskesmas Ngemplak - Damayanti, Vita, Dr. Faizah Betty Rahayuningsih, A.S.Kep., M.Kes (2017)
Postpartum hemorrhage can occur due to failure of the myometrium to contract after delivery so that the uterus in a state of deep relaxation, less good and mushy. One way that the muscle contractions of the uterus -otot remain good until the end of parturition is with early mobilization and simple movements such as gymnastics parturition. Knowledge and attitudes of pregnant women about postpartum exercise for this is still insufficient to support them do gymnastics parturition. Steps can be taken to improve the knowledge of pregnant women about postpartum gymnastics is the provision of health education. This study aims to determine the effect of health education on knowledge and attitudes about gymnastics parturition in pregnant women in the third trimester Ngemplak health center. This research is a quantitative research using pre-experimental research design type one group pretest posttest. The study population was the third trimester pregnant women who reside in excl. Ngemplak or numbering around 56 people in the month of September with the criteria trimeseter Maternity III (months 7-9 of pregnancy) as well as pregnant women during their pregnancy in Puskesmas Ngemplak. Sample research counted 36 pregnant women was obtained by purposive sampling. Collecting data using questionnaires, while data analysis using paired samples t-test. Conclusion The study showed knowledge of pregnant women about postpartum gymnastics before health education is largely sufficient and less, then after health education and mostly quite good. The attitude of pregnant women about postpartum gymnastics before health education is largely negative, then after health education was largely positive. There are differences in knowledge and attitudes about postpartum in pregnant women trimester III after health education at the health center before and after giving Ngemplak health education where knowledge and attitudes of health education after higher than before health education.